Edukasi Industri Komoditi Berjangka Kepada Masyarakat Sebagai Sarana Memperkuat Branding Perusahaan - Mukti, Aging Sarana; Irbayuni, Sulastri (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
At present, commodity futures trading is still not widely recognised by the public. Lack of trust from the public towards brokerage companies is one of the causes. Therefore, there is a need for innovation aimed at increasing public trust and awareness of brokerage companies. The way that can be done is to provide education about the commodity futures industry to the public as a means of strengthening company branding. With strong company branding, it can increase public trust and awareness of brokerage companies. The methods used in this community service are problem identification, implementation and assessment. The results of the community service carried out are the implementation of education to the community can increase the trust and enthusiasm of the community towards brokerage companies.